Fungsi dan Tujuan Pengembangan Kurikulum Pendidikan Agama Islam Multikultural di Madrasah Tsanawiyah Al-Fakhriyah Makassar - Inayah, Siti Nur; Tang, Muhammad (CV. Creative Tugu Pena, 2024)
This research purpose to explore and analyze the functions and purposes of developing a multicultural Islamic religious education curriculumat Al-Fakhriyah Makassar Islamic Junior High School. The researcher use qualitative research method with a case study approach, data collection using participatory observation, structured and unstructured interviews, and documentation, and then the data is processed by analyzing it through an interactive model proposed by Miles and Huberman.. The results of this research is the functions of developing a multicultural curriculum at Al-Fakhriyah Makassar Islamic Junior High School include: (1) serving as a guide for educators gives learning and evaluation especially multicultural-based learning, (2) as pillars or guidelines is required by educators, and (3) as a catalyst for students development. While, the purpose of developing a multicultural curriculum at Al-Fakhriyah Makassar Islamic Junior High School is to produce students with comprehensive and multicultural capabilities in line with the vision and mission of the school. The development of the Islamic religious education curriculum has proven to enhance students competencies, achievements, and tolerance. However, some Islamic religious education subjects have difficulty in completing them. Therefore, as educators must more attentions to their teaching models to ensure that learning objectives are successfully achieved Keywords: Curiculum Development, The Islamic Religious Education, Multicultural